The culture and politics of regime change in Italy, c. 1494-c.1559
1 online resource (viii, 274 pages)
Keywords: "This volume offers the first comprehensive survey of regime change in Italy in the period c.1494-c.1559. Far from being a purely modern phenomenon, regime change was a common feature of life in Renaissance Italy - no more so than during the Italian Wars (1494-1559). During those turbulent years, governments rose and fell with dizzying regularity. Some changes of regime were peaceful; others were more violent. But whenever a new reggimento took power, old social tensions were laid bare and new challenges emerged - any of which could easily threaten its survival. This provoked a variety of responses, both from newly established regimes and from their opponents. Constitutional reforms were proposed and enacted; civic rituals were developed; works of art were commissioned; literary works were penned; and occasionally, aspects of material culture were pressed into service, as well. Comparative in approach and broad in scope, it offers a provocative new view of the diverse political, culture, and economic factors which ensured the survival (or demise) of regimes - not only in 'major' polities like Florence, Rome, and Venice, but also in less-well studied regions like Savoy. This book will appeal to researchers and students alike interested in cultural, military and political history"--